Injection techniques for bulk cell seeding decellularised vascular scaffolds. (1st January 2012) - Sheridan, William S.; Duffy, Garry P.; Murphy, Bruce P.
Tissue engineering small diameter vascular grafts requires excessive culture times to produce an appropriate extracellular matrix (ECM). The use of decellularised exogenous tissue as a scaffold has the potential to overcome this limitation due to the preformed ideal ECM architecture that remains after decellularisation. While this scaffold reduces ECM maturation times cell seeding is difficult due to the high density of decellularised tissue, particularly within the medial layer of the scaffold. In this study, we investigated the possibility of direct injection of vascular cells within decellularised porcine carotid arteries through the use of micro-needles inserted into the medial layer prior to decellularisation. The results indicate that these injection methods are feasible and provide a method for quickly bulk cell seeding decellularised scaffolds.